Students’ Perceptions of a Google Forms-Based Escape Room for Learning the Past Tense: A Case Study at SMA Negeri 4 Cirebon - Karimah, Mika Anisatun; Mulatsih, Devi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study explores the use of a Google Forms-based Escape Room as a tool for teaching the simple past tense in an EFL classroom with limited technological resources. Conducted at SMA Negeri 4 Cirebon, the study involved 34 tenth-grade students who participated in a series of Escape Room activities designed to enhance grammar learning. Using a qualitative case study approach, data were collected through questionnaires, interviews, and non-participant observations. Findings reveal that the majority of students found the Escape Room method enjoyable, motivating, and helpful for understanding past tense rules, particularly verb forms and time adverbs. Many students reported increased confidence and better memory retention after the activity. However, challenges such as internet connectivity issues, game mechanics, and confusion over past tense usage were also noted. Thematic analysis shows that while the method promoted engagement and provided contextualized grammar practice, individual learning preferences and technical barriers influenced student experiences. This study suggests that a Google Forms-based Escape Room is a feasible and effective strategy for grammar instruction in low-tech environments and provides insights for educators seeking to implement gamified learning with minimal resources.